2022
DOI: 10.12688/f1000research.73610.1
|View full text |Cite
|
Sign up to set email alerts
|

Students’ attitudes and coping strategies relating to online learning during the COVID-19 pandemic: A cross-sectional study

Abstract: Background: The emergence of the COVID-19 pandemic has forced most classes at the tertiary education level to be held online or in a digital mode. This study investigates Multimedia University (MMU) students’ attitudes and coping strategies in relation to online learning classes during the COVID-19 pandemic.   Methods: This is a cross-sectional analysis among students at the MMU campus in Malaysia. Student respondents were chosen using simple random sampling. They answered online surveys developed through Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…While Transcendent Orientation, Positive Attitude, and Orientation to Problem predicted higher levels of general health, the avoiding coping strategy showed negative effects. The results support those of previous studies, which showed that positive coping strategies are important variables able to moderate the relationships between pandemic-related difficulties (both personal and academic) and the self-reported level of health [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While Transcendent Orientation, Positive Attitude, and Orientation to Problem predicted higher levels of general health, the avoiding coping strategy showed negative effects. The results support those of previous studies, which showed that positive coping strategies are important variables able to moderate the relationships between pandemic-related difficulties (both personal and academic) and the self-reported level of health [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the study of Savitsky et al [ 42 ], positive coping strategies (i.e., humour) were found to be associated with positive attitudes (i.e., low anxiety levels). More recently, Rahmat et al [ 43 ] found that positive attitudes toward online learning (or acceptance) significantly correlated with the use of positive coping strategies (e.g., planning, positive reframing, active coping), while negative attitudes were significantly associated with negative strategies (e.g., self-blame, denial, substance use).…”
Section: Introductionmentioning
confidence: 99%
“…In further, Rahmat et al [49] conducted a study involving 353 students at a multimedia university in Malacca, Malaysia reported that 8 out of 14 coping strategies had a moderate correlation with students' attitudes towards online learning. This shows that students who have a positive attitude towards online learning are likely to use positive coping strategies which are active coping, positive reframing, planning, and acceptance.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%
“…Likewise, highly resilient people tend to engage in active solutions [ 36 ], and largely choose problem-focused coping [ 37 ]. Stronger resilience was related to lower levels of anxiety during the COVID-19 pandemic [ 38 ]. Emotional coping is often considered less adaptive [ 39 ].…”
Section: Introductionmentioning
confidence: 99%